Partial ring hydrogenation of naphthols over supported metal catalysts in supercritical carbon dioxide solvent - Mine, Eiichi; Haryu, E.; Arai, K.; Sato, T.; Sato, O.; Sasaki, A.; Rode, C. V.; Shirai, M. (Chemistry Letters, 2005)
Selective ring hydrogenation of naphthols to tetrahydronaphthols and tetralones proceeded at 323 K over a charcoal supported rhodium catalyst in supercritical carbon dioxide.

Ring hydrogenation of naphthalene and 1-naphthol over supported metal catalysts in supercritical carbon dioxide solvent - Shirai, M.; Rode, C. V.; Mine, Eiichi; Sasaki, A.; Sato, O.; Hiyoshi, Norihito (Catalysis Today, 2006)
Catalytic ring hydrogenations of naphthalene and 1-naphthol were studied over several supported metal catalysts in supercritical carbon dioxide solvent at low temperature. Higher concentration of hydrogen in supercritical carbon dioxide and lower reaction temperature were responsible for higher catalyst activity and selectivities to the desired partial ring hydrogenated products as compared with those observed in organic solvent for the same catalyst. (c) 2006 Elsevier B.V. All rights reserved.
8th International Conference on Carbon Dioxide Utilization, Univ Oslo, Oslo, NORWAY, JUN 20-23, 2005
Keywords: 1-naphthol; Hydrogenation; Naphthalene; Supercritical carbon dioxide; supported metal catalyst